Effectiveness of the Combination of Alum (Al₂(SO₄)₃) and Calcium Hydroxide (Ca(OH)₂) Coagulants in the Removal of Manganese (Mn) Using the Coagulation-Flocculation Process: Efektivitas Kombinasi Koagulan Alum (Al2(SO4)3) dan Kalsium Hidroksida (Ca(OH)2) pada Penghilangan Logam Mangan (Mn) Menggunakan Proses Koagulasi-Flokulasi - Simanullang, Samuel Putra Mandiri; Afandy, Moh. Azhar; Sawali, Fikrah Dian Indrawati (Department of Chemistry - Universitas Bangka Belitung, 2024)
A technique for reducing the contamination of heavy metals in wastewater is the coagulationflocculation method. The approach has various advantages, including a simple process, readilyavailable chemicals, inexpensive equipment costs, and an excellent capacity to remove pollutants. The goal of this research is to see how well Mn-containing wastewater can be reduced using alum and calcium hydroxide as coagulants. The adsorption capacity of the coagulant combination in the floc generation phase of the coagulation-flocculation process can also be calculated. The technique used is coagulation-flocculation, with modifications made to the coagulant content and stirring duration. The data was then evaluated using an Atomic Absorption Spectrophotometer (AAS) to assess the decrease Mn concentration in wastewater. According to the experiments, the combination of alum and calcium hydroxide coagulants with a mass composition ratio of alum:calcium hydroxide (150 mg:50 mg) and a stirring time of 15 minutes has the highest efficiency of 89.35% and is directly proportional to the adsorption capacity value of 446.75mg/gram.